How to strengthen the Polish venture capital market? An analysis of the solutions in selected countries - Fałat-Kilijańska, Ilona (Jak wzmocnić polski rynek venture capital? Analiza przyjętych rozwiązań w wybranych krajach, 2015)
The history of venture capital funds has shown that they are crucial for the promotion of innovation and competitiveness of the economy. By funding projects that are considered by others as too risky, they contribute to the increase in the number of modern enterprises as well as create jobs and constitute a significant participant in the capital market. This article aims to identify the factors having an impact on the condition of the Polish market of venture capital investments. An analysis of the system solutions adopted by the US and European leaders in the venture capital market indicates that of greatest importance are the legal regulations on the organisational forms of funds and their fiscal transparency as well as those on the system of tax reliefs and exemptions and pension funds’ participation possibilities. Such aspects as the corporate income tax rate and the capital gains tax rate proved to be of secondary importance for the operation of venture capital funds
Nauki o Finansach = Financial Sciences, 2015, Nr 4 (25), s. 9-23
Keywords: investments; venture capital; innovation; entrepreneurship; przedsiębiorczość; inwestycje; innowacje